Investigating the Determinants of Eco-Friendly Purchase Intention among Malaysian Consumers in the Food and Beverage Industry - Yee Huei Lok; Fatin Hazimah Mohd Hasri; Felix Frall Anak Draman; Fifi Ellia Najwani Mesuan; Tew Chin En Fion; Rahul Mayur; Daisy Mui Hung Kee (AIBPM Publisher, 2026)
The global shift toward sustainability has greatly influenced consumer behavior, particularly within Malaysia’s growing food and beverage (FB) sector. Yet, a persistent gap remains between consumers’ eco-friendly behavior and their actual purchasing decisions. This study investigates the determinants of eco-friendly purchase intention among Malaysian consumers in the FB industry, focusing on environmental concern, environmental knowledge, and perceived consumer effectiveness (PCE). A quantitative research design was employed using an online survey administered to 200 Malaysian consumers. The findings reveal that all three variables exert a significant positive influence on eco-friendly purchase intention, with environmental knowledge emerging as the strongest predictor. The findings provide valuable practical insights into the key determinants influencing Malaysian consumers’ purchase intention toward eco-friendly FB products. The result can assist FB industry in creating effective marketing strategies that promote sustainability while guiding consumers toward environmentally responsible purchasing decisions.